2005
DOI: 10.1002/chem.200500092
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Asymmetric Synthesis of Stereochemically Labile Aldehyde Helicates and Subsequent Chirality Transfer Reactions

Abstract: Helical complexes formed between aluminum tris(2,6-diphenylphenoxide) (ATPH) and five different aldehydes have been prepared and structurally characterized by X-ray diffraction. It was found that [Al(OC6H3Ph2)3PhCHO] (2), [Al(OC6H3Ph2)3(4-CH3C6H4CHO)] (3), [Al(OC6H3Ph2)3(4-tBuC6H4CHO)] (4), and [Al(OC6H3Ph2)3(p-CH3OC6H4CHO)] (5) all crystallize as conglomerates, while crystals of [Al(OC6H3Ph2)3(o-CH3OC6H4CHO)] (6) are racemic. Supramolecular CH/pi interactions between molecules in crystals of 2-5 that enable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Although several examples of CH À p bonds as a supramolecular control element have been previously described, [11] our helicoidal architecture constitutes a rare example in which this type of interaction is responsible for an assembly process to give an unexpected helical superstructure. [10,12] Additionally, we observed the assembly of different chains through another intermolecular CH À p interaction established between the C10 À H10B methyl of pyrazol ring and the phenyl (C14 À C19) ring. The H10B-(centroid of phenyl) distance has a value of 3.325 and the degree of displacement of H10B from the centre of phenyl ring (D offset ) is 1.89 .…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Although several examples of CH À p bonds as a supramolecular control element have been previously described, [11] our helicoidal architecture constitutes a rare example in which this type of interaction is responsible for an assembly process to give an unexpected helical superstructure. [10,12] Additionally, we observed the assembly of different chains through another intermolecular CH À p interaction established between the C10 À H10B methyl of pyrazol ring and the phenyl (C14 À C19) ring. The H10B-(centroid of phenyl) distance has a value of 3.325 and the degree of displacement of H10B from the centre of phenyl ring (D offset ) is 1.89 .…”
mentioning
confidence: 77%
“…There are few cases of aluminium complexes containing ligands that are wrapped around the metal much like in a helicate. [10] The helical surface for complex 2 (Figure 1) was characterised in the solid state by X-ray crystallography (discussed below). The molecular structure of complex 2 ( Figure 2) exhibits a dimeric-like arrangement that is achieved through a bridging dianionic thioacetamidate fragment.…”
mentioning
confidence: 99%
“…Nevertheless, this was the first report of absolute asymmetric synthesis of an organometallic reagent; previous work on absolute asymmetric synthesis through total spontaneous resolution generally relies on photochemical rearrangement in chiral crystals or total spontaneous resolution of prochiral substrates, such as keto-compounds or alkenes. [7][8][9][10][11] We have more recently studied organometallic reagents displaying chirogenic α-carbon atoms (Scheme 1), since subsequent reaction with an electrophile may trap the configuration at the α-carbon atom and generate a configurationally inert organic product. We recently published the absolute Scheme 1. asymmetric synthesis of such a reagent, bis(1-η 1 -indenyl)-bis(3-picoline)zinc (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…This would give rise a chirogenic center, and any enantiomeric excess could be determined by classical methods. We have previously shown that the reaction between solid methyllithium and chiral crystals of tris{2,6‐diphenylphenolato‐( p ‐tolylaldehyde)}‐aluminum gave 1‐ p ‐tolylethanol with an enantiomeric excess of 17% . To test this hypothesis, the reaction between 1 and solid dimethylmagnesium was investigated.…”
Section: Resultsmentioning
confidence: 99%